Restricting direct interaction of CDC37 with HSP90 does not compromise chaperoning of client proteins - Smith, Jennifer R. (2013)
The HSP90 molecular chaperone plays a key role in the maturation, stability and activation of its clients, including many oncogenic proteins. Kinases are a substantial and important subset of clients requiring the key cochaperone CDC37. We sought an improved understanding of protein kinase chaperoning by CDC37 in cancer cells. CDC37 overexpression in human colon cancer cells increased CDK4 protein levels, which was negated upon CDC37 knockdown. Overexpressing CDC37 increased CDK4 protein half-life and enhanced binding of HSP90 to CDK4, consistent with CDC37 promoting kinase loading onto chaperone complexes. Against expectation, expression of C-terminus truncated CDC37 (ΔC-CDC37) that lacks HSP90 binding capacity did not affect kinase client expression or activity; moreover, as with wildtype CDC37 overexpression, it augmented CDK4-HSP90 complex formation. However, although truncation blocked binding to HSP90 in cells, ΔC-CDC37 also showed diminished client protein binding and was relatively unstable. CDC37 mutants with single and double point mutations at residues M164 and L205 showed greatly reduced binding to HSP90, but retained association with client kinases. Surprisingly, these mutants phenocopied wildtype CDC37 overexpression by increasing CDK4-HSP90 association and CDK4 protein levels in cells. Furthermore, expression of the mutants was sufficient to protect kinase clients CDK4, CDK6, CRAF and ERBB2 from depletion induced by silencing endogenous CDC37, indicating that CDC37’s client stabilising function cannot be inactivated by substantially reducing its direct interaction with HSP90. However, CDC37 could not compensate for loss of HSP90 function, showing that CDC37 and HSP90 have their own distinct and non-redundant roles in maintaining kinase clients. Our data substantiate the important function of CDC37 in chaperoning protein kinases. Furthermore, we demonstrate that CDC37 can stabilise kinase clients by a mechanism that is not dependent on a substantial direct interaction between CDC37 and HSP90, but nevertheless requires HSP90 activity. These results have significant implications for therapeutic targeting of CDC37.